2022
DOI: 10.1038/s41375-022-01584-3
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 mutations contribute to the progression of MDS due to disruption of antitumor cellular defense: a study on patients with lower-risk MDS

Abstract: Patients with lower-risk myelodysplastic syndromes (LR-MDS) have a generally favorable prognosis; however, a small proportion of cases progress rapidly. This study aimed to define molecular biomarkers predictive of LR-MDS progression and to uncover cellular pathways contributing to malignant transformation. The mutational landscape was analyzed in 214 LR-MDS patients, and at least one mutation was detected in 137 patients (64%). Mutated RUNX1 was identified as the main molecular predictor of rapid progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…In our study mutations in RUNX1 and ASXL1 defined distinct subgroups within spliceosome mutated MDS potentially driving progression. This is concordant with previous reports demonstrating that RUNX1 and ASXL1 mutations contribute to the progression in lower-risk MDS, are more frequently mutated in rapidly progressing patients [11] and correlate with unfavorable outcome in MDS [12,13]. We previously reported that RUNX1 mutations are independent negative prognostic factors for OS and AML transformation in SF3B1 mut MDS [14].…”
supporting
confidence: 92%
“…In our study mutations in RUNX1 and ASXL1 defined distinct subgroups within spliceosome mutated MDS potentially driving progression. This is concordant with previous reports demonstrating that RUNX1 and ASXL1 mutations contribute to the progression in lower-risk MDS, are more frequently mutated in rapidly progressing patients [11] and correlate with unfavorable outcome in MDS [12,13]. We previously reported that RUNX1 mutations are independent negative prognostic factors for OS and AML transformation in SF3B1 mut MDS [14].…”
supporting
confidence: 92%
“…Abnormalities occur at SNV/Indels levels (Abnormalities in user’s upload data section). Moreover, ARID1A is involved in 2 pathways including the RUNX1 pathway, which plays an important role in the development of leukemia (Pathways section) ( Kaisrlikova et al, 2022 ). The literature section indicates that ARID1A is observed in a variety of cancers including bladder cancer ( Saito et al, 2018 ; Cao et al, 2020 ), ovarian cancer ( Kim et al, 2016 ), liver cancer ( Sun et al, 2017 ) and colon cancer ( Mathur et al, 2017 ; Iftekhar et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…36,37 Although these mutations have not been included in the guidelines as progression factors, some of them assuredly predict poor outcomes and even result in the development of acute myeloid leukemia. 38,39 On the other hand, previous studies of HMA (decitabine)treated patients with MDS-EB showed that genetic relapse can predate morphological relapse. 40,41 This indicates that gene examination after treatment is also vitally important to monitor tumor burden.…”
Section: Discussionmentioning
confidence: 99%